Resonance coupling in hybrid gold nanohole–monolayer WS2 nanostructures. (June 2019) - Chen, Xuexian; Wang, Hao; Xu, Ning-Sheng; Chen, Huanjun; Deng, Shaozhi
Graphical abstract: Highlights: Resonance coupling has been demonstrated in hybrid nanostructures composed of individual gold NH coated with monolayer WS2 flake. The near-field electromagnetic field enhancements associated with the plasmon resonances of an individual gold NH was revealed using s-SNOM technique. A Rabi splitting energy of 162 meV was determined at room temperature, which to the best of our knowledge is the largest value ever reported using individual metallic or dielectric nanocavities coupled with the monolayer TMDCs. Abstract: Planar metallic nanoholes exhibit plasmonic resonances capable of confining electromagnetic fields down to the nanoscale, which can benefit the light–matter interactions at the nanoscale. In addition, they are more geometrically compatible with state-of-the-art microfabrication techniques in comparison with other types of plasmonic nanostructures of curved surfaces or protrusions. Two-dimensional transition metal dichalcogenides (TMDCs) are promising materials for studying light–matter interactions owing to their excellent optical properties. Herein, we propose a resonance plasmon–exciton coupling system based on the integration of monolayer tungsten disulfide (WS2 ) with an individual plasmonic gold nanohole. Our results demonstrate that Rabi splitting exceeding 162 meV can be achieved in planar TMDC/metal nanostructures at room temperature. We believe that such hybrid systems provide a simple and robust single nanostructure design that can be used to manipulate light–matter interactions at the nanoscale.